Computer-human interaction research and applications : first International Conference, CHIRA 2017, Funchal, Madeira, Portugal, October 31-November 2, 2017, Revised selected papers /: first International Conference, CHIRA 2017, Funchal, Madeira, Portugal, October 31-November 2, 2017, Revised selected papers. (2019) - Unknown
No abstract available